Foot Hula Hoop Game: An Innovative Approach to Stimulating Agility in Early Childhood Education - Anwar, Irana; Pramono; Tirtaningsih, Munaisra Tri (Universitas Pendidikan Ganesha, 2024)
The issue identified in this study is the low level of agility in children aged 5-6 years, which affects their motor skills. One way to address this issue is through games that can stimulate the agility of children. The aim of this study is to develop a foot hula hoop game that is suitable for stimulating agility in children aged 5-6 years. This research employs the Research and Development (R&D) method, adapted from the Borg and Gall model as modified by Sugiyono. The study follows nine steps: identifying potential and problems, data collection, product design, product design validation, product design revision, small group trial, revision based on small group trial results, large group trial, and final product refinement. Quantitative data were collected through questionnaires validated by early childhood game experts, content experts, and user validation (teachers) during the small and large group trials. Qualitative data were obtained from expert feedback, teacher input, initial interviews, and observational notes. The research subjects were 5-6-year-old children, with 6 children involved in the small group trial and 41 children in the large group trial. The conclusion of this study is that the foot hula hoop game is highly suitable for stimulating agility in children aged 5-6 years.